PERUBAHAN KECERNAAN PATI, PROTEIN DAN KARAKTERISTIK TEPUNG SORGUM (Sorghum bicolor (L.) Moench) SELAMA FERMENTASI - , ZULMAN EFENDI,STP; , Dr. Ir. Yudi Pranoto, STP. MP. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Sorghum as an important cereal crop is rich carbohydrates and protein but the nutritional value of sorghum is diminished because of low digestibility value of the starch and protein. One effort to increase the starch and protein digestibility of sorghum flour is by fermentation treatment. This study aims to know changes in starch, protein digestibility and characteristics properties of sorghum flour during fermentation. Fermentation of sorghum flour was conducted using Completely Randomized Design with two factors included type and period of fermentation. Both of fermentation such as spontaneous and Lactobacillus plantarum sub plantarum strain NBRC 15891 isolate were done at 37Â°C from 0 up to 36 hours dan samples were observed every 4 hours. The bacterial number, pH and titratable acidity of fermentation in the fermenting medium were analyzed. Starch and protein digestibility, tannin levels, brightness, microstructure appearance, and pasting properties of fermented sorghum flour were also analyzed. The results of the bacterial number during 36 hours spontaneous fermentation showed that total aerobic bacteria increased from 6.10 to 11.52 log 10 CFU/ml, Lactic Acid Bacteria (LAB) increased from 6.33 to 11.00 log10 CFU/ml, proteolytic bacteria increased from 4.19 to 7.37 log10 CFU/ml, pH decreased from 5.98 to 3.36 with a concomitant increase in titratable acidity from 0.21% to 1.37%, starch and protein digestibility, soluble protein, and tannin-free increased from 44.36% to 76,07%, from 45.87% to 67.38%, from 0.55% to 1.06% and from 0.57% to 0.84%, respectively. The bacterial number during 36 hours fermentation by L. plantarum showed that total aerobic bacteria increased from 6.86 to 9.50 log10 CFU/ml, LAB increased from 6.78 to 9,44 log10 CFU/ml, proteolytic increased from 5,26 to 6,9 log 10 CFU/ml, pH decreased from 5.80 to 3.34 with a concomitant increase in titratable acidity from 0.25% to 1.38%, starch and protein digestibility, soluble protein, and tannin-free from increased from 47.34% to 78,41%, from 41.81% to 80.31%, from 0.73% to 1.94%, and from 0.94% to 1.39%, respectively. The increase of coliform by L. plantarum fermentation from 4,54 to 5,00 log 10 CFU/ml was lower than spontaneous fermentation from 5,67 to 7,26 log 10 CFU/ml. The Optimal starch digestibility of sorghum flour was obtained from the fermentation of 28 hours by L. plantarum for 84.59% with protein digestibility, brightness, gelatinization temperature and peak viscosity were 76.88%, 82.49, 79Â°C and 689 cP, respectively while microstructure appearance no compact in comparison to control.